Enhancing efficacy of special education early teachers: the external and psychological resilience factors perspectives - Abdul Jalil, Amalina Ulya; Ahmad, Nor Aniza (Human Resource Management Academic Research Society, 2018)
The incremental value of efficacy enhancement of pre-teachers can also be predicted form the perspective of their resilience factors. The purpose of this study is to determine the relationship between resilience factors with personal and general teaching efficacy among special education pre-service teachers. The resilience factor includes both external and psychological factors. The sample of this study consists of 194 special education pre-service teachers in Malaysian public universities. Descriptive analysis is carried out to determine the teaching efficacy level. The Pearson correlation is conducted to determine the relationship between resilience with teaching efficacy among pre-teachers of special education. Regression analysis is used to predict teaching efficacy based on resilience. The findings show high levels of confidence in personal teaching efficacy, while moderate low levels of confidence in general teaching efficacy. On overall basis, the resilience factors shows a high moderate level. The Pearson correlation generally shows that resilience factors have a positive and significant relationship with teaching efficacy. The regression analysis shows that resilience factor of conversion is an essential predictor for teaching efficacy. The implication of this study is for special education pre-service teachers to perceive both psychological and external resilience factors to enhance their teaching efficacy, professionally.